2007
DOI: 10.1097/01.iyc.0000264482.35570.32
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Interactions With Infants Who Have Complex Multiple Disabilities

Abstract: This article describes primary outcomes of the development and field-testing of a curriculum Promoting learning through active interaction with 27 infants and their caregivers and early interventionists in 2 different states. The curriculum was designed to provide a systematic approach to supporting interactions with infants who have sensory impairments and complex multiple disabilities and who are at the preintentional level of communication. Participating infants had both a visual impairment and hearing loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…Earlier work at the SFCCC with modern ICTs in BLNs revealed that the technology can help bridge significant geographical distances (Hanson, Magnusson, and Sennemark 2011). Chen, Klein, and Haney (2007) highlighted that web-based or online instruction to train personnel in low-incidence disabilities can work well for professional development. They researched an online course designed to train early interventionists to support parents in interacting with their infants who had multiple disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work at the SFCCC with modern ICTs in BLNs revealed that the technology can help bridge significant geographical distances (Hanson, Magnusson, and Sennemark 2011). Chen, Klein, and Haney (2007) highlighted that web-based or online instruction to train personnel in low-incidence disabilities can work well for professional development. They researched an online course designed to train early interventionists to support parents in interacting with their infants who had multiple disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, findings indicate that the caregiver-infant relationship is strengthened by caregiver behavior that (a) emphasizes mutually enjoyable, fine-tuned caregiver-infant interactions, (b) encourages infant competence, and (c) shows warmth and affection that reinforces and engages the infant . This lack of responsiveness or initiation requires specific strategies on the part of caregivers to engage infants in turn taking and other early interactions (Chen et al, 2007;Dale, 2005;Reinhartsen, 2000). Prolonged stays in the neonatal intensive care unit or frequent hospitalizations or both may interrupt the natural caregiving process and limit opportunities for mutually enjoyable interactions.…”
Section: Caregiver Interactions and Interventionsmentioning
confidence: 99%
“…This professional development course was composed of face-to-face meetings and online instruction on implementing Promoting Learning Through Active Interaction , a family-centered curriculum that has been designed and field tested to address the early communication needs of infants with multiple disabilities (Chen, Klein, & Haney, 2007). Many of these children are preintentional in their socialcommunicative behavior and have developmental delay, motor problems, visual impairment, hearing loss, and medical needs.…”
mentioning
confidence: 99%
“…Active Support tends to focus on this increased level of involvement as a means of engaging people in meaningful functional activities, whereas Intensive Interaction focuses primarily on promoting social interaction. Interventions specifically for people with sensory impairments including congenital deafblindness are PLAI (Chen, Klein, & Haney, 2007), Contact (Janssen, Riksen-Walraven, & van Dijk, 2003a), and the intervention strategies suggested by the Deafblind International Network on Communication (Rødbroe & Janssen, 2006a, 2006bSouriau, Rødbroe, & Janssen, 2008;Souriau, Rødbroe, & Janssen, 2009), all of which, like Intensive Interaction, are grounded in infant development theory.…”
Section: Staff-client Interactionsmentioning
confidence: 98%